Institutional economics: contributions to the development of holistic economics : essays in honor of Allan G. Gruchy - Adams,Adam (Bosten, 1980)
This book is one of the most important collections of essays to appear in the field of institutional economics in recent years. INSTITUTIONAL ECONOM ICS assesses and extends the work of Allan G. Gruchy, Professor Emeritus at the University of Maryland, College Park. Gruchy is well-known among econ mists for his MODERN ECONOMIC THOUGHT (1917), CONTEMPORARY ECONOMIC THOUGHT (1972), and COMPARATIVE ECONOMIC SYSTEMS (second edition, 1972). His efforts to synthesize institutional economics and his advocacy of national economic planning have made him perhaps the best known figure among contemporary institutional economists. This collection embodies Gruchy's major precept: that we must always be concerned with where the economy is going, that institutional economics has important con tributions to make to meeting this concern, and that the national economy needs to be looked at as part of an evolving society and political system.
Keywords: Economics. 2. Economics policy. 3. Underdeveloped countr